Efektivitas Implementasi SFAS No. 1 dalam Penyusunan Laporan Keuangan dan Dampaknya terhadap Standar Pelaporan - Kanya Lailatul Ulya; Atikah Rakhmawati (BADAN PENERBIT STIEPARI PRESS, 2022)
The implementation of Statement of Financial Accounting Standards (SFAS) No. 1, now known as Statement of Financial Accounting Standards (PSAK) No. 1, is a crucial step in improving the transparency and consistency of financial statements. This study explores the effectiveness of SFAS No. 1 implementation in the financial statement preparation process and its impact on reporting standards. Through data analysis of the financial statements of companies implementing SFAS No. 1 as well as interviews with accounting professionals, this study identifies the challenges and benefits of implementing the standard. The results show that the implementation of SFAS No. 1 improves the accuracy and transparency of financial statements, but also faces challenges in terms of complexity and comprehension that require further attention. The impact on reporting standards includes improvements in the quality of financial information and strengthening compliance with generally accepted accounting principles. This research provides insights into how the implementation of SFAS No. 1 may affect reporting practices and suggests strategies to overcome the challenges.